The Ecdysis Triggering Hormone System, via ETH/ETHR-B, Is Essential for Successful Reproduction of a Major Pest Insect, Bactrocera dorsalis (Hendel) - Shi, Yan; Liu, Tian-Yuan; Jiang, Hong-Bo; Liu, Xiao-Qiang; Dou, Wei; Park, Yoonseong; Smagghe, Guy; Wang, Jin-Jun (Frontiers in Physiology, 2019)
Ecdysis triggering hormone (ETH), released by the Inka cells, is a master hormone in regulating the ecdysis process in insect. Here we investigated the presence and role of the ETH signaling in the female adult of the oriental fruit fly, Bactrocera dorsalis (Hendel) that is one of the most important invasive pest insects in agriculture worldwide. In the female adult, ETH was confirmed in the Inka cells at the tracheae by immunostaining and also in vitro exposure to ETH stimulated the isolated corpora allata of adult in activity. Then we prepared cDNA of females at 0, 5, 10, 15, and 20 days after adult eclosion, and RT-qPCR showed that the expression pattern of ETH and its receptor ETHR-B started from a peak at the day of adult eclosion (day 0), then dropped to basal levels and increased again between day 10 and 15 which is also the period corresponding to ovary growth. In contrast, ETHR-A was absent with Ct values of >33. The expression patterns of the ecdysteroid-producing Halloween genes Spook and Shade, and the vitellogenin genes Vg1, Vg2, and Vg3 co-occurred with peak levels at days 10–15, and also juvenile hormone acid methyltransferase (JHAMT) showed increased levels on day 15. Further in RNAi assays to better understand the role of ETH and ETHR, dsRNA was injected to adult and this led to a respective decrease in expression of 62 and 56% for ETH and ETHR-B, while ETHR-A stayed absent with Ct values of 33. In these RNAi-females, there was an apparently decreased expression for JHAMT and Vg2, together with a significant decrease of the JH titer and egg production. Injection of the JH mimetic methoprene could rescue Vg2 expression and egg production. Upstream, in dsETH/dsETHR-injected females, 20-hydroxyecdysone (20E) injection rescued the transcriptions of ETH and ETHR and also egg production. In summary, our results shed more light on the pivotal role that the ETH peptide hormone and its receptor ETHR-B play an essential role in the reproduction of the female adult of B. dorsalis, via the regulation of JH and vitellogenin, which are controlled by a pulse of 20E.